2000
DOI: 10.1111/1467-8721.00078
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity-Related Sources of Stress and Their Effects on Well-Being

Abstract: Early research on ethnicity focused on the stereotyped thinking, prejudiced attitudes, and discriminatory actions of Euro-Americans. Minoritygroup members were viewed largely as passive targets of these negative reactions, with low self-esteem studied as the main psychological outcome. By contrast, recent research has increasingly made explicit use of stress theory in emphasizing the perspectives and experiences of minority-group members. Several ethnicity-related stressors have been identified, and it has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 12 publications
2
106
0
Order By: Relevance
“…Physical bullying by peers is another form of abuse that is gaining attention, given data documenting its relationship to adverse mental health outcomes (20), including binge eating (21). Finally, studies of health and psychological problems among black Americans have identified discrimination based on ethnicity as an important ethnicity-specific risk factor (22,23). The present study examined the contribution of four types of abusive experiences to risk for the development of binge eating disorder: childhood sexual abuse, physical abuse, bullying by peers, and discrimination.…”
Section: (Am J Psychiatry 2002; 159:1902-1907)mentioning
confidence: 99%
“…Physical bullying by peers is another form of abuse that is gaining attention, given data documenting its relationship to adverse mental health outcomes (20), including binge eating (21). Finally, studies of health and psychological problems among black Americans have identified discrimination based on ethnicity as an important ethnicity-specific risk factor (22,23). The present study examined the contribution of four types of abusive experiences to risk for the development of binge eating disorder: childhood sexual abuse, physical abuse, bullying by peers, and discrimination.…”
Section: (Am J Psychiatry 2002; 159:1902-1907)mentioning
confidence: 99%
“…Contrada et al (2000) identify "stereotype confirmation-concern"-that is, "the chronic apprehension about appearing to confirm an ethnic stereotype"-as one of the top sources of ethnicity-related stress. On the other hand, "own-group conformity pressure" is a commonly felt stressor which, for example, may discourage African-Americans from excelling academically to avoid "acting white".…”
Section: Literature Reviewmentioning
confidence: 99%
“…Primary concepts include ethnic discrimination, stereotype threat, and own-group conformity pressure (Contrada, et al, 2000). Subsumed under ethnic discrimination would be stress associated with attributional ambiguity (Crocker, Major & Steele, 1998).…”
Section: Ethnicity-related Stressmentioning
confidence: 99%
“…Subsumed under ethnic discrimination would be stress associated with attributional ambiguity (Crocker, Major & Steele, 1998). Contrada, et al, (2000) note the attention has shifted from the perpetrators of prejudice and discrimination to the inner phenomenology of the individual who is the target of discrimination. Further, the contribution of stress theory and recent broadening of outcomes to include psychological and physical wellbeing are acknowledged.…”
Section: Ethnicity-related Stressmentioning
confidence: 99%
See 1 more Smart Citation